ANALYSIS OF THE JALAWASTU AREA AS A SUSTAINABLE CULTURAL TOURISM - Jafar Mukhlis; Stevie Louise Estella De Costa (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2021)
Cultural tourism offers culture in the form of tourist objects that are tangible or concrete, intangible or abstract, as well as those that are living culture and cultural heritage. The potential of the Jalawastu Area has unique cultural values such as traditional ceremonial events and traditions that are still being maintained. This study aims to see the Jalawastu Area as a cultural tourism destination in Brebes Regency. The research method used is a descriptive method that aims to describe or describe phenomena or relationships between the phenomena being studied systematically, factually, and accurately (Kusmayadi, 2000). In addition, the descriptive method is a way of analyzing comprehensive data in the framework of explaining the conditions or characteristics of an area that occur as a particular consideration according to Densin. Based on the results of the analysis, the conclusion is that the development of the tourism heritage area of the Jalawastu Cultural Village has great potential as a cultural tourism destination, and the aspect of the analysis and culture that is owned by the existence of the Jalawastu Cultural Village has a unique architecture encourages the creation of a unique and distinctive domestic image. If the Jalawastu Cultural Village is developed with good management and planning, it will encourage the formation of a tourism heritage area with the main attraction being a tourist attraction for traditional ceremonies and traditional arts as historical and cultural tourism. The research recommendations include: on the product side, improving quality in the packaging of cultural and artificial products in the tourism heritage of the Jalawastu Cultural Village in an attractive tour package, adding supporting activities such as the tangible and tangible potential of Brebes Regency in the tourism area of the Jalawastu Cultural Village as a symbol To introduce the Brebes area as a whole to domestic and foreign tourists, the program is to innovate for the heritage tourism attractions of the Jalawastu Cultural Village to make it more attractive.